PENINGKATAN KESTABILAN SISTEM ENERGI BEBASIS PLTB MELALUI CRITICAL CLEARING TIME YANG TERHUBUNG SMART GRID - Fitriani, Fitriani; Mantofani, Risal; Muhtar, Muhdalifah (Universitas Nusa Cendana, 2024)
Wind Power Plants (PLTB) are a vital renewable energy source in the global transition towards clean energy. PLTB holds great potential for reducing reliance on fossil fuels and enhancing the stability of power systems. However, unpredictable wind power fluctuations can challenge system stability. To address this, smart systems like the Smart grid are needed. The Smart grid is an evolution of traditional power systems equipped with dynamic optimization techniques to improve real-time efficiency, reliability, and sustainability. Additionally, transient stability analysis is crucial for maintaining system stability during disturbances. One method used is the Critical Clearing Time (CCT) calculation, which determines the critical disconnection time from the onset of the disturbance until synchronization is lost. This study uses transient analysis simulations on the Sungguminasa – Maros power system, utilizing the Power System Analysis Toolbox (PSAT) under MATLAB. By integrating PLTB with the Smart Grid, it is expected that better coordination between power system components can be achieved, enhancing not only the system’s reliability and stability but also optimizing overall energy efficiency.